Analysis of Corruption Settlement for Obligor Deviations of Bank Indonesia Liquidity Assistance (BLBI) - Hasbullah, Hasbullah (Universitas Negeri Semarang (UNNES), 2019)
The settlement of the BLBI Corruption Case was only focused on the mistakes of former IBRA Chairperson Syafruddin Arsyad Temenggung who issued paid settlement letter to Sjamsul Nursalim as a BLBI obligor which caused 4.58 trillion in financial losses, even though the SKL issuance contained legal slices of the state administration process and civil affairs. The corruption case of the former Chairperson of the IBRA has diverted us all to the main point of corruption errors in the BLBI distribution. Distribution of the Bank Indonesia Liquidity Assistance Facility (BLBI) with a total of 144.53 trillion, from the distribution recorded based on BPK-RI Audit No. 34 I / XII / 11/2006, there was a distribution deviation amounting to 138.44 trillion, but the BPK audit by law enforcement has never been carried out until now. Therefore the problem is focused on two main things, namely whether the settlement of the BLBI Corruption crime in the case of the IBRA chairman issuing SKL to Sjamsul Nursalim has resolved the BLBI corruption case and how the law enforcement policy in BLBI corruption settlement has cost the state 138,44 trillion . Using a normative juridical method that is qualitative in nature, the research results show that the settlement of BLBI corruption in the case of the IBRA chairman issuing SKL to Sjamsul Nursalim is not the case for BLBI irregularities and even in the legal doctrine of the case is not a corruption case due to a legal clash state administration and civil law. and there has been a transfer of corruption eradication in the case of BLBI distribution which has cost the country a total of 138.44 trillion, because law enforcers must enforce the law against alleged BLBI corruption with criminal mechanisms and if possible civilian efforts.